Ocean bottom hydrophone sgy-files of seismic refraction and wide-angle data from profile P02 during SONNE cruise SO267 - Anna Jegen; Anke Dannowski; Heidrun Kopp (PANGAEA, 2022)
The dataset contains ocean bottom hydrophone data acquired on profile P02 during RV Sonne Expedition SO267 (project ARCHIMEDES I) to the Lau Basin, Southwestern Pacific. 27 OBS recorded the seismic survey successfully and returned data for the two consecutively performed acquisitions, once with a 50m shot interval and once with a 170m shot interval. The stations 207, 215 and 229 suffered from recorder errors, which prevented or interfered with the redording of data and thus their analysis.